Maternal Immune Response During Pregnancy and Vertical Transmission in Human Toxoplasmosis - Gómez-Chávez, Fernando; Cañedo-Solares, Irma; Ortiz-Alegría, Luz Belinda; Flores-García, Yevel; Luna-Pastén, Héctor; Figueroa-Damián, Ricardo; Mora-González, Juan Carlos; Correa, Dolores (Frontiers in Immunology, 2019)
Toxoplasmosis is a parasitic zoonosis distributed worldwide, caused by the ingestion of contaminated water/food with the parasite Toxoplasma gondii. If a pregnant woman is infected with this parasite, it may be transmitted to the fetus and produce ocular, neurological, or systemic damage with variable severity. The strength and profile of mother's immune response have been suggested as important factors involved in vertical transmission rate and severity of clinical outcome in the congenitally infected fetus. The aim of this work was to evaluate a possible relation between the mother's immune response during pregnancy and congenital transmission to the fetus. We obtained peripheral blood from T. gondii infected pregnant woman and tested it for anti T. gondii (IgG1, IgG2, IgG3, IgG4, and IgA) in serum. Peripheral blood mononuclear cells (PBMCs) were isolated to analyze the in vitro effect of soluble T. gondii antigens on proliferation and production of cytokines. We found that IgG2-4 and IgA antibodies and lymphocytes proliferation, especially CD4+, CD8+, and CD19+ were positive in a higher proportion of cases in transmitter than in non-transmitter women. Furthermore, IgG2-3 and IgA anti-Toxoplasma antibody levels were higher in those mothers who transmitted the infection than in those who did not. Interestingly, a higher proportion of positive cases to IFN-γ and negatives to the immunoregulatory cytokine TGF-β, were related to T. gondii vertical transmission. Our descriptive results are consistent with the paradoxical previous observations in murine models of congenital toxoplasmosis, which suggest that an increased immune response that protects the mothers from a disseminated or severe disease, and should protect the fetus from infection, is positively related to parasite transmission.